Sediment and pore water investigations in thermokarst terrain near Utqiagvik, Alaska - Seemann, Fabian; Jenrich, Maren; Lindemann, Justin; Eulenburg, Antje; Weiner, Mikaela; Mollenhauer, Gesine; Meyer, Hanno; Overduin, Pier Paul; Grosse, Guido; Jones, Benjamin; Strauss, Jens (PANGAEA, 2025)
This dataset comprises sediment and pore water analyses from sediment cores taken in April 2022 close to Utqiagvik, Alaska. An undisturbed upland, one drained lake basin, two thermokarst lakes, a semi-open thermokarst lagoon and Elson Lagoon were sampled during fieldwork. Sedimentological and hydrochemical analyses were conducted at the Permafrost Research Section (AWI Potsdam), radiocarbon dating at the Mini Carbon Dating System (MICADAS) laboratory (AWI Bremerhaven) and the isotope data has been generated in the ISOLAB Facility (AWI Potsdam).
Keywords: Alaska; Permafrost; pore water; sediment; talik; thermokarst